Supervisi Akademik Memoderasi Pengaruh Kompetensi dan Komit-men Organisasi terhadap Kinerja Guru - Undang Lukman Hakim; R Basiya (Jurnal Bisnis dan Ekonomi, 2018)
This study aims to analyze the effect of teachers competence and organizational commitment to teachers performance of senior high school in Kesatrian Education Foundation 67 Semarang with academic supervision as a moderation variable. The number of population was 102 teachers and the entire population used as sample research (census method). Data collection techniques used survey method with kuesiuoner as data collection tool. The testing technique of the questionnaire using validity test with factor analysis test and reliability test with alpha cronbach. Methods of data analysis with descriptive analysis and regression moderation analysis. The result of the analysis shows that teachers competence has a positive and significant effect on teachers performance. Organizational commitment has no effect on teachers performance. Academic supervision has a positive and significant effect on teachers performance. Academic supervision moderates the influence of teachers competence on teachers performance. Academic supervision does not moderate the influence of organizational commitment to teachers performance.